2013
DOI: 10.3126/noaj.v1i1.8126
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous trigger finger release

Abstract: BACKGROUND: Trigger finger is caused by formation of nodule or thickening of A1 pulley by its fibrocartilage metaplasia resulting in entrapment of the flexor tendon. Conservative treatment of this condition consists of NSAIDs, splint immobilization and steroid injection into the tendon sheath. Failure of the conservative treatment is the indication of an open release. Percutaneous release of trigger finger is advised by several authors. The purpose of this prospective study is to evaluate the results of percut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…Our series has no persistence of triggering. Patients satisfaction in both the series (Pandey BK et al 2 and HA CW et al 3 ) were 93% and 97% respectively. Our series at the end of one year had a mean VAS score of 0.44, and 95.0% had Quinells grade 0, while preoperatively the mean VAS score was 8.16 and (Chart 1) 60% had Quinells grade 3 and 30% had grade 4 (Chart 2).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our series has no persistence of triggering. Patients satisfaction in both the series (Pandey BK et al 2 and HA CW et al 3 ) were 93% and 97% respectively. Our series at the end of one year had a mean VAS score of 0.44, and 95.0% had Quinells grade 0, while preoperatively the mean VAS score was 8.16 and (Chart 1) 60% had Quinells grade 3 and 30% had grade 4 (Chart 2).…”
Section: Discussionmentioning
confidence: 84%
“…Ha CW et al 3 had 185 percutaneous trigger fingers release using specially designed HAKI knife and had 12 (6.48%) digits with persistent triggering. Pandey BK et al 2 had done percutaneous release of 58 fingers with 18 G needle and had 2 digits with persistence of triggering. Our series has no persistence of triggering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Study reports percutaneous release had overall success of 51/58 (97%) with no clinical evidence of digital nerve injury or tendon bowstringing after release with 18G needle. 15 Similarly, 97% excellent and good results is reported using 18G needle. 16 We had no complications of nerve, vascular or tendon injuries, or tendon bowstringing.…”
Section: Discussionmentioning
confidence: 93%
“…11,20,21 Nevertheless other authors reported excellent and good results in thumb too. [12][13][14][15][16][17] In order to prevent digital nerve damage, the needle should be held above the tendon in the midline of the thumb and radial approach should be avoided.…”
Section: Discussionmentioning
confidence: 99%